2019
DOI: 10.3390/agronomy9090542
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits and Risks for Soil Health Derived From the Use of Organic Amendments in Agriculture

Abstract: The use of organic amendments in agriculture is a common practice due to their potential to increase crop productivity and enhance soil health. Indeed, organic amendments of different origin and composition (e.g., animal slurry, manure, compost, sewage sludge, etc.) can supply valuable nutrients to the soil, as well as increase its organic matter content, with concomitant benefits for soil health. However, the application of organic amendments to agricultural soil entails a variety of risks for environmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 218 publications
(286 reference statements)
3
118
0
4
Order By: Relevance
“…Biochar is a carbon-rich, solid material obtained by biomass (manure, sewage sludge, wood biomass and crop residues) pyrolysis in an oxygen-limited environment [18][19][20][21]. The effects of their addition to agricultural soils depend on a number of factors, including feedstock properties and processing conditions, application rate, soil type, environmental conditions, and crop species [22,23]. About the latter, the yield response to compost or biochar applications are often contrasting; generally, either positive or negative and sometimes also neutral effects on crop yield and quality have been reported [13,24].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a carbon-rich, solid material obtained by biomass (manure, sewage sludge, wood biomass and crop residues) pyrolysis in an oxygen-limited environment [18][19][20][21]. The effects of their addition to agricultural soils depend on a number of factors, including feedstock properties and processing conditions, application rate, soil type, environmental conditions, and crop species [22,23]. About the latter, the yield response to compost or biochar applications are often contrasting; generally, either positive or negative and sometimes also neutral effects on crop yield and quality have been reported [13,24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to both inform and sensitize governments and the society in general, the World Health Organization presented a list of the most critical antibiotic-resistant pathogen species ( Tacconelli et al, 2018 ). Although inevitably much more attention has been paid to the magnitude of this problem in hospital settings, the role of the environment on the emergence and dissemination of antibiotic resistance has been relatively recently recognized ( Garbisu et al, 2018 ; Urra et al, 2019a , b , c ).…”
Section: Introductionmentioning
confidence: 99%
“…Meelu and Singh (1991) showed that 4 t ha -1 poultry manure along with 60 kg N ha -1 as urea produced grain yield of crop similar to that with 120 kg Nha -1 as urea alone. But direct application of poultry manure have negative effect on soil health (Urra et al, 2019). That's why it needs be composted.…”
Section: Introductionmentioning
confidence: 99%